Combustion characteristics of n-heptane spray combustion in a low temperature reform gas/air environment. (1st June 2021) - Zhong, Shenghui; Xu, Shijie; Bai, Xue-Song; Hadadpour, Ahmad; Jangi, Mehdi; Zhang, Fan; Du, Qing; Peng, Zhijun
Highlights: A novel n-heptane reform gas combustion is investigated using LES and t-PDF model. The n-heptane reform gas is shown to suppress the ignition and increase the liftoff. The reforming gas weakens the NTC ignition behavior of n-heptane. The combustion process involves inner diffusion flame and outer lean premixed flame. The premixed flame in the surrounding reforming gas/air mixture enhances soot and suppresses NOx emission. Abstract: This paper presents a large eddy simulation study of n-heptane spray combustion in an n-heptane low temperature reform (LTR) gas environment in a constant volume combustion chamber, under conditions relevant to single-fuel reactivity controlled compression ignition (RCCI) combustion engines. The LTR gas is made up of partially oxidized intermediate species from rich n-heptane/air mixture in an external constant temperature reformer. It is found that a higher reform temperature results in a longer ignition delay time of the n-heptane spray and a higher liftoff length, due to the chemical effect of the LTR gas and the difference in the reaction zone structures. A significantly different spray flame structure is identified in the RCCI case from that of single-fuel spray combustion. After the onset of high temperature ignition, a double-layer flame structure is established in the RCCI case, with a diffusion flame layer and a lean premixed flame layer. The lean premixed flame affects the flow field, which significantly suppresses the mixing around the spray tip. As a result, the RCCI case exhibits a lower NOx formation but a higher soot formation than the single-fuel case.